In vitro evaluation of 56 coronary artery stents by 256-slice multi-detector coronary CT - Steen, Henning; André, Florian; Korosoglou, Grigorios; Mueller, Dirk; Hosch, Waldemar P.; Kauczor, Hans-Ulrich; Giannitsis, Evangelos; Katus, Hugo (European journal of radiology, 2011)
Objective - We sought to investigate stent lumen visibility of 56 coronary stents with the newest 256-multi-slice-CT (256-MDCT) technology for different reconstruction algorithms in an in vitro model. - Background - Early identification of in-stent restenosis (ISR) is important to avoid recurrent ischemia and prevent acute myocardial infarction (AMI). Since angiography has the disadvantage of high costs and its invasiveness, MDCT could be a convenient and safe non-invasive alternative for detection of ISR. - Material and methods - Percentages of in-stent lumen diameter and in-stent signal attenuation (measured as contrast-to-noise ratio (CNR)) of 56 coronary stents (group A ≤2.5mm; group B=2.75-3.0mm; group C=3.5-4.0mm) were evaluated in a coronary vessel in vitro phantom (iodine-filled plastic tubes) employing four different reconstruction algorithms (XCD, CC, CD, XCB) on a novel 256-MDCT (Philips-iCT, collimation=128mm×0.625mm; rotation time=270ms; tube current=800mAs with 120kV). Analysis was conducted with the semi-automatical full-width-at-half-maximum (FWHM) method. P-values <0.05 were regarded statistically significant. - Results - In-stent lumen diameter >60% for group C stents was significantly larger and CNR was significantly lower (both p<0.05) for sharp kernels (CD; XCD) when compared to groups A/B. The FWHM-method showed significantly smaller in-stent lumen diameter (p<0.05) when compared to the manual method. - Conclusion - 256-MDCT could potentially be employed for clinical assessment of stent patency in stents >3.0mm when analysed with cardio-dedicated sharp kernels, although clinical studies corroborating this claim should be performed. However, stents ≤3.0mm reconstructed by soft kernels revealed insufficient in-stent lumen visualisation and should not be used in clinical practice. Further improvements in spatial and temporal image resolution as well as reductions of radiation exposure and image noise have to be accomplished for the ambitious goal of characterising both CT coronary artery anatomy and in-stent lumen.
Online verfügbar: 3 September 2010
Gesehen am 21.10.2022